2014
DOI: 10.1186/1940-0640-9-11
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone brief intervention applications for risky alcohol use among university students: a randomized controlled study

Abstract: BackgroundBrief interventions via the internet have been shown to reduce university students’ alcohol intake. This study tested two smartphone applications (apps) targeting drinking choices on party occasions, with the goal of reducing problematic alcohol intake among Swedish university students.MethodsStudents were recruited via e-mails sent to student union members at two universities. Those who gave informed consent, had a smartphone, and showed risky alcohol consumption according to the Alcohol Use Disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
228
1
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(249 citation statements)
references
References 40 publications
5
228
1
15
Order By: Relevance
“…For example, in smoking cessation studies, a higher frequency of texts can be sent around the date that a smoker has set for quitting 29. This is also important for interventions on alcohol use where the text messages can be targeted at heavy drinking occasions 30.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in smoking cessation studies, a higher frequency of texts can be sent around the date that a smoker has set for quitting 29. This is also important for interventions on alcohol use where the text messages can be targeted at heavy drinking occasions 30.…”
Section: Introductionmentioning
confidence: 99%
“…Apps based on principles like this are said to have indirect evidence to support them until direct evidence is obtained. But as previously mentioned, studies have shown significant discrepancy between evidence for a treatment modality in regular clinical settings compared to that in mobile device app setting (Gajecki et al 2014;Heffner et al 2015;Kertz et al 2017). Thus, precautions are warranted for indirect evidence as such discrepancy could lead to not only lack of efficacy but also potential harm to users (Gajecki et al 2014;Heffner et al 2015;Kertz et al 2017).…”
Section: Discussionmentioning
confidence: 92%
“…Assessing the evidence supporting ASD app is critical, as at least in other areas of psychiatry studies have shown a significant discrepancy between presumed benefit and actual clinical applicability or efficacy of apps (Gajecki et al 2014;Heffner et al 2015;Kertz et al 2017). Despite numerous apps claiming to be evidence-based, this purported evidence often refers only to evidence-based principles such as cognitive behavioral therapy which may or may not work equally well when delivered in a new digital format and app design (Fletcher-Watson et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…BinDhim et al, 2014;Borland et al, 2013;Bricker et al, 2014;Buller et al, 2014;Haug et al, 2014;Hertzberg et al, 2013;Kirchner et al, 2013;Meredith et al, 2014;V. Patel, Nowostawski, Thomson, Wilson, & Medlin, 2013;Ploderer et al, 2014;Reitzel et al, 2014; Whittaker, 2011) Alcohol 12 (34.3%) (Bendtsen & Bendtsen, 2014;Dulin et al, 2014;Gajecki et al, 2014;Gamito et al, 2014;Haug et al, 2014;Kauer, Reid, Sanci, & Patton, 2009;Matsumura, Yamakoshi, & Ida, 2009;McTavish et al, 2012;Renner, 2012;Yu et al, 2012) Heroin 2 (5.7%) Epstein et al, 2009) Cocaine 1 (2.9%) (Freedman, Lester, McNamara, Milby, & Schumacher, 2006) General 3 (8.6%) (Campling, 2011;Ingersoll et al, 2014; Bendtsen & Bendtsen, 2014;BinDhim et al, 2014;Borland et al, 2013;Bricker et al, 2014;Buller et al, 2014;Dulin et al, 2014;Hasin et al, 2014;Haug et al, 2014;Ingersoll et al, 2014;Ploderer et al, 2014;Renner, 2012;Whittaker, 2011;Yu et al, 2012) Relapse prevention 3 (8.6...…”
Section: Discussionunclassified
“…Yet the security of this procedure is uncertain as it is possible for codes to be broken or cracked with modern computing methods (Wei, Murugesan, Kuo, Naik, & Krizanc, 2013). Although most of the apps that used encryption methods also de-identified the data collected BinDhim et al, 2014;Boyer et al, 2012;Gajecki, Berman, Sinadinovic, Rosendahl, & Andersson, 2014;Gamito et al, 2014;Renner, 2012;, collecting a wide range of data, including geo-location, renders it possible to construct a data profile that may identify the user (Gasson et al, 2011).…”
Section: User Anonymitymentioning
confidence: 99%